Letter from J. E. Sullivan to the Coordinator of Research and Development - Sullivan, J. E. (1945)
The letter sketches the specifications for a partial pressure indicator for use in aircraft, and notes that a prototype has already been constructed. The recipient may be a member of the Navy's Research and Development department. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Beckman Instruments, Inc.